Use of Papaya Plant (Carica papaya) Latex for Making Cottage Cheese from Cow Milk - Jesmin, Mst. Marzia; Sarker, Md. Abid Hasan; Islam, Mohammad Ashiqul; Harun-ur-Rashid, Md.; Siddiki, Mohammad Shohel Rana Siddiki (Journal of the Bangladesh Agricultural University, 2024)
The study was carried out on milk clotting activity of the crude proteolytic enzyme (papain) from different parts of papaya plant (Carica papaya). Cottage cheese was prepared using whole cow milk collected from Bangladesh Agricultural University Dairy Farm. Diluted papaya latex (4 drops in 100 ml distilled water) was added and thoroughly mixed for coagulation of milk from different parts of the papaya plant. The treatment samples were named as A: mature papaya; B: immature papaya; C: papaya tree leaf; D: lower part stem and E: upper part stem. In case of organoleptic evaluation, it was observed that differences in scores for flavor, body and texture, finish, color, and total score were insignificant (p>0.05). In chemical analysis, significant (p< 0.05) differences were found in total solids, fat and ash contents among the different type of cheese samples. The highest total solids was found in samples B (56.24%) where the highest protein (30.97%), carbohydrate (9.30%), fat (22.67%) and ash (2.90%) content were observed in samples C, A, E and C, respectively. On the other hand, the lowest (p<0.05) acidity (0.73%) was recorded in sample B. Finally, it was evident that latex (papain) from different parts of papaya plant can be used in cottage cheese preparation. J Bangladesh Agril Univ 19(1): 85–90, 2021 https://doi.org/10.5455/JBAU.13262